BASELINE VALUES OF OXIDATIVE STRESS BIOMARKERS IN CATTLE - Nath, Rita; PRASAD, RAM LAKHAN; SARMA, SATYA (Indian Journal of Animal Production and Management, 2017)
The goal of this study is to summarize the baseline values of both enzymatic and nonenzymatic oxidative stress biomarkers in cattle. Blood samples were collected from ten(10) crossbred cattle from Instructional Bovine Farm, Ranchi Veterinary College, BAU,Ranchi that were screened on the basis that the animals were clinically healthy. Differentantioxidants biomarkers were estimated using standard methods. The superoxidasedismutase, glutathione peroxidase and glucose-6-phosphate dehydrogenase activities inhemolysate of healthy animals were 391.023±25.930 U/L, 123.556±5.208 U/ mg and11.907±1.287 U/gm Hb respectively. The malonyl dialdehyde produced was 1.904±0.132nmol/g Hb. The serum albumin and uric acid concentration were 4.325±0.222 gm/dl and2.927 ± 0.159 mg/dl respectively. The concentration of total serum bilirubin, direct bilirubin(conjugated) and indirect bilirubin (non-conjugated) in the healthy animals in the study were0.467 ± 0.055, 0.329 ± 0.015 and 0.138 ± 0.023 mg/dl respectively. This study will provide adatabase that will be useful in clinical Biochemistry.